Determination of Yield and Economics of Three Chili Hybrids (Capsicum annuum L.) in Cuatro Caminos, San Gabriel, Jalisco, Mexico - Ricardo, González Mateos; Gregorio, González Tiburcio; Juan, Pereyda Hernández; Vianey, González Zavaleta Sandra (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
This study analyze the performance, investment and profitability of three chili hybrids of the Company “González Produce RESE SPR DE RL”, in Cuatro Caminos, San Gabriel, Jalisco, Mexico. The chili pepper is consumed fresh within the country and is also exported to the United States. Different species and varieties of chili peppers are grown,5 from broad, jalapeños, serranos (green), poblano, mirasol (known as dry guajillo), bell or bell pepper, anaheim and caloro. The experimental unit was one hectare per hybrid, with fertigation and mulching. The beds were 1.20 m wide, with double-row planting and 0.30 m of separation between plants. The yield (t ha-1) was calculated with the number of harpillas harvested, multiplied by 30 kg for Caloro and Jalapeño, and 25 kg for Serrano. Economic income, cost / benefit ratio, equilibrium point and invested weight gain were estimated. Chile Serrano registered 1,658 arpillas ha-1, equivalent to 41 t ha-1, surpassed Caloro and Jalapeño by 8.39 and 36.0%, respectively. Caloro’s production cost was $ 32,631.66 USD ha-1 (Exchange rate 1 dollar = 17.0493, 10 February, 2024), 34 and 51% higher than Serrano and Jalapeño. The income obtained from the sale of Serrano pepper was $ 56,838.11 USD, 3.9 and 31% higher than Caloro and Jalapeño. The C / B ratio for Serrano was 1.85; Caloro, 1.74 and Jalapeño, 1.26. The equilibrium point was reached for Caloro at 7.08 t ha-1, Serrano – Platino and Jalapeño –Valquiria with 10.21 and 20.72 t ha-1, respectively. The prices of chili, as with most agricultural products, are a function of the demand and supply in the market and the harvest season, that is, the first harvests have a higher value in the market.